Acanthocytes Identified in Huntington’s Disease - Yu, Yueyi; Lu, Yuanyuan; Wang, Fen; Lu, Yan; Xie, Beijia; Meng, Xiaosheng; Tang, Yi (Frontiers in Neuroscience, 2022)
Background: Neuroacanthocytosis (NA) and Huntington’s disease (HD) are neurodegenerative conditions that share clinical symptoms and imaging findings, despite their distinct genetic etiologies. Usually, the presence of acanthocytes can help narrow the differential diagnosis of a familial choreiform disorder, as the diagnosis of NA syndrome is supported by the presence of acanthocytes in peripheral blood. In this study, we demonstrate four patients who present with HD and acanthocytosis. Methods: We retrieved the data of 40 HD patients with fresh peripheral blood screened for erythrocytes in our hospital from 2014 to 2022. Of these 40 patients, four patients with acanthocytes were recruited for this study. Patients’ investigations included clinical and laboratory studies, HTT gene sequencing, and whole-exome sequencing. Fresh peripheral blood was screened for erythrocytes by scanning electron microscopy. Results: The four adult patients were Han Chinese and unrelated. The age ranged from 45 to 61 years, with a disease duration of 4-10 years. The main neurological features at diagnosis included progressive involuntary movements, psychiatric changes, and dementia. Genetic analysis showed an expansion at the HTT gene. The mean proportion of acanthocytes was mild (6-10%) elevated in patient one and high (>20%) elevated in patients 2-4 by scanning electron microscopy examination. Conclusions: Our study illustrates that HD can combine with acanthocytosis, which may expand the clinical phenotype. Even though the primary gene defect appears to be predominately directed at the brain, a peripheral defect can be seen in HD. Our study highlights the complexity and diversity of HD.